TRANSPORT AND STORAGE OF POTASSIUM IN THE EARTH?S UPPER MANTLE AND TRANSITION ZONE: AN EXPERIMENTAL STUDY TO 23 GPA IN SIMPLIFIED AND NATURAL BULK COMPOSITIONS - Konzett Ju.; Fei Y. (My University, 2000)
We have investigated the stability and composition of potassium amphibole and its high-pressure breakdown product phase X in synthetic peralkaline and subalkaline KNCMASH (K2O–Na2O–CaO–MgO–Al2O3–SiO2–H2O) and natural KLB-1 peridotite bulk compositions between 10 and 23 GPa at 800–1800°C. In the KNCMASH system, potassium amphibole reaches its upper pressure stability limit at 13–15 GPa at ?1400°C. In the natural KLB-1 bulk composition, potassium amphibole breaks down between 12 and 13 GPa at 1200°C. Phase X is a hydrous potassium–magnesium silicate with variable stoichiometry, a general formula K2–xMg2Si2O7Hx with x = 0–1, and a maximum possible H2O content of 3·5 wt %. Electron microprobe analytical totals suggest H2O contents of ?1–2 wt % and a decrease in H2O contents with increasing pressure. In both KNCMASH and KLB-1 systems, phase X coexists with Mg2SiO4 + garnet + high-Ca clinopyroxene + low-Ca clinopyroxene ± fluid. Phase X breaks down between 20 and 23 GPa at 1500–1700°C to form K-hollandite + γ-Mg2SiO4 + majorite + Ca-perovskite + fluid. The upper temperature stability limit of phase X was located in the subalkaline KNCMASH system between 1400 and 1600°C at 14 GPa and at >1700°C at 20 GPa, the latter being at least 200°C above an average current mantle adiabat. Thus, phase X could store and transport both water and potassium not only in subduction zone settings, but also in convecting mantle down to the transition zone–lower-mantle boundary. Phase X would also be an eminently suitable host for Rb, Cs, Ba or Pb.